The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1093/oxfordjournals.pcp.a029406
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Stress-Related Expression of 1-Aminocyclopropane-l-carboxylate Oxidase Gene Family in Nicotiana glutinosa L.

Abstract: Three full length 1-aminocyclopropane-1-carboxylate (ACC) oxidase cDNA clones (pNG-ACO1, 1,254 bp; pNG-ACO2, 1,198 bp; and pNG-ACO3, 1,053 bp) were isolated from the TMV-treated leaf cDNA library of Nicotiana glutinosa plant. They share a high degree of sequence identity (78-81%) throughout the coding regions but are divergent within the 3'-untranslated regions. The gene-specific probes were prepared using these regions to investigate the differential expression of the ACC oxidase gene family in various organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 0 publications
3
44
1
Order By: Relevance
“…Of the nine genes known to change expression during senescence, only two (NtACO1 and NtACO3) were induced as anticipated for the senescing plants; these genes are also known to be induced by other signals, such as wounding and viral infection (Kim et al, 1998). Therefore, the presented results taken together support the hypothesis that the highly induced expression of CYP82E4 in young green leaves of the KD lines is likely not triggered by senescing signals.…”
Section: Ntmthfr1 Negatively Affects Cyp82e4 Expressionsupporting
confidence: 76%
See 2 more Smart Citations
“…Of the nine genes known to change expression during senescence, only two (NtACO1 and NtACO3) were induced as anticipated for the senescing plants; these genes are also known to be induced by other signals, such as wounding and viral infection (Kim et al, 1998). Therefore, the presented results taken together support the hypothesis that the highly induced expression of CYP82E4 in young green leaves of the KD lines is likely not triggered by senescing signals.…”
Section: Ntmthfr1 Negatively Affects Cyp82e4 Expressionsupporting
confidence: 76%
“…4). Leaf senescence is known to induce both ACS and ACO enzymes sharply, but the formation of ACC is often considered to be the rate-limiting step on the pathway (Kim et al, 1998;Wang et al, 2002;Lin et al, 2009). The lack of ACS induction, therefore, is consistent with the lack of increase in ethylene production in the analyzed transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In potato, highly increased expression of all ACO genes, in both low and high temperature was observed (Nie et al 2002). Wounding stimulated principally the transcription of some ACO paralogs: ST-ACO1 (Nie et al 2002), NG-ACO3 (Kim et al 1998), PP-ACO1 (Ruperti et al 2001), MA-ACO1 (Pan and Lou 2008). In contrast, Choudhury et al (2008b) observed that in preclimacteric banana fruit, wounding down-regulated the expression of both MA-ACS1 and MA-ACO1 genes and thus inhibited ethylene production.…”
Section: Stress Responsesmentioning
confidence: 98%
“…Based on this result, the transcript levels of key enzymes involved in the ET synthesis pathway, namely ACC synthase and ACC oxidase, were determined along with quantification of the production of ET. On the basis of previous studies of different ACC synthase isoforms in Arabidopsis (Skottke et al, 2011;Li et al, 2012) and ACC synthase and oxidase in tomato (Lincoln et al, 1993;Kim et al, 1998;Cohn and Martin, 2005;Shi and Zhang, 2014;Yim et al, 2014), three candidate transcripts for each enzyme (ACS1a, ACS2, ACS6 for ACC synthase, and ACO1, ACO 1-like and ACO 4-like for ACC oxidase) with suspected roles in pathogenesis processes were selected.…”
Section: Overlap Of Upregulated Genes Among Baba- Oligandrin-and Patmentioning
confidence: 99%